Porównywalność danych w międzynarodowych badaniach marketingowych (wybrane zagadnienia) - Grabowska, Aleksandra (Data Comparison in International Marketing Research (Selected Problems), 2006)
The paper presents some issues which concern the problem connected with data comparison in international marketing research. The author attempts to verify the hypothesis that data's comparison in the international marketing research can be disrupted by culture aspect. To make sure that the marketing decisions are taken on the basis of information which reflects reality the researchers should throughly analyze the culture and social differences of researched subjects.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 69-78